Effectiveness of whistleblowing procedure and strategy in construction developer companies: a conceptual paper / Muhammad Afham Kamaruzaman and Kartina Alauddin - Kamaruzaman, Muhammad Afham; Alauddin, Kartina (Universiti Teknologi MARA, Cawangan Melaka, 2018)
Whistleblowing can be illustrated as an essential element of the primary and effective approach to reduce corruption by producing a flow of procedure in channelling unethical activities complaints to the authorities. This importance in dealing with corruption problem by implementing whistleblowing procedure is to promote transparency for all business relationship between parties involved. In Malaysia, the National Key Results Area (NKRA) has indicated that eradicate corruption to be achieved under the Government Transformation Program (GTP). Thus, this research aim is to propose a framework and state variables to be tested empirically in future studies related to whistleblowing implementation in developer organizations in Malaysia. The possible finding is the administrative procedures of the ‘appropriate authorities’ responsible for implementing the process could equally be strengthened. Current procedure of whistleblowing policy implemented have made the observer faced with various forms of behavioural options including keeping silent to remain in the organization, reporting to colleagues, confronting the wrongdoers, engaging in internal and external whistleblowing or exiting the company. The comparison is made against the objectives which are to identify the procedure of channelling whistleblowing procedure in different developer companies and to determine the difficulties of whistleblowing in developer companies. This paper is enforced by in-depth literature review, primarily in the most recent research that supports the whistleblowing strategy in construction industry. Thus, by analysed all the details will give some illustration on what to be proposed as a strategy of an effective whistleblowing that well suited to be implemented in a developer companies.